PENGARUH MEDIA WORDWALL TERHADAP HASIL BELAJAR MATEMATIKA SISWA KELAS II SDN TIDUNG - Nurul Aulia Tahir; Andi Mulawakkan Firdaus; Marup (STKIP Subang, 2025)
This study aims to determine the effect of Wordwall media on the mathematics learning outcomes of second-grade students at SDN Tidung. The research employed a pre-experimental one-group pretest-posttest design with 20 students from class II A as the sample. The instruments used were learning achievement tests (pretest and posttest) and student activity observation sheets. The results showed that the average pretest score of 49.00 increased to 79.00 in the posttest. The N-Gain test indicated a moderate level of improvement, while the one-sample t-test confirmed a significant difference between pretest and posttest results. Therefore, the application of Wordwall media positively influences students’ mathematics learning outcomes.